Eluxadoline for the treatment of diarrhoea-predominant irritable bowel syndrome. (2nd July 2016) - Scarpellini, Emidio; Laterza, Lucrezia; Ianiro, Gianluca; Tack, Jan; Abenavoli, Ludovico; Gasbarrini, Antonio
ABSTRACT: Introduction : Irritable bowel syndrome (IBS) treatment is challenging physicians because of its multifactorial physiopathology. In particular, abdominal pain and diarrhea management lack one unique effective pharmacological remedy. Opioid receptors, present in the central nervous system (CNS) and the enteric nervous system (ENS), are involved in visceral sensitivity and gastrointestinal motility control. To date only a few opioid receptor modulators are currently in use for the treatment of IBS but with dosage limitations due to the early development of severe constipation. Areas covered : In this drug evaluation manuscript we review the irritable bowel syndrome therapeutic needs and chemistry, pharmacokinetics and -dynamics, clinical study results with the new opioid receptor ligand eluxadoline for the treatment of diarrhea-predominant irritable bowel syndrome (IBS-D). Expert opinion : Eluxadoline shows a peculiar pharmacological profile with μ-opioid agonism and δ-opioid antagonism actions. Its efficacy over placebo for the treatment of abdominal pain and diarrhea in IBS-D has been demonstrated in short- and long-term clinical studies in humans. Its safety has been evaluated in the same studies. Interestingly, eluxadoline showed a low rate of constipation development in IBS patients in comparison with known effects of other opioid receptor modulators. Patients with a history of acute pancreatitis should not be treated with eluxadoline.